124 OUTCOME OF SPEECH AND LANGUAGE THERAPY CLINICAL DYSPHAGIA ASSESSMENT FOLLOWING AN INTERDISCIPLINARY SWALLOW SCREEN. (18th November 2021) - Maher, J; Ryan, S; King, L; Sayers, K; Donnellan, C; Pillay, I
Abstract: Background: A 7 question non-validated swallow screen (Any reported swallowing difficulties? Any coughing with food or fluids? Any choking? Does food get stuck when eating? Any recurrent chest infections? Any pain when swallowing? Any difficulty swallowing tablets?) is used by an integrated care team for older persons to prioritise referrals to the Speech and Language Therapy (SLT) service. This study identified the proportion of patients screened who appropriately required a clinical dysphagia assessment and intervention. Methods: This was a retrospective study from September 2020 to June 2021. Patients were assessed by the Clinical Specialist SLT who determined if swallow impairment was present and whether intervention was required. Age, gender and clinical frailty score were documented. Patients who resided out of the catchment area or who had already received an SLT service were excluded. Results: The average age was 80 years, range 67–103. The male to female ratio was 2:1 and the average clinical frailty score (CFS) was 5. N = 42(32%) screened positive. N = 29(69%) attended for SLT assessment. N = 27(93.1%) had a swallow impairment identified. N = 20 were discharged following a single intervention and 9 required further SLT intervention. Conclusion: Presbyphagia is generally asymptomatic and results from age related anatomical and physiological changes, reduced functional reserve and sarcopenia. Older adults compensate for these difficulties and do not seek assistance. Presbyphagia may progress to dysphagia, resulting in adverse outcomes. The high rate of SLT confirmed swallow impairment and need for SLT intervention highlights a need to prospectively refine and validate this 7 question swallow screen.